Strategi Badan Usaha Milik Desa (BUMDes) Dalam Upaya Meningkatkan Pendapatan Asli Desa Di Desa Taro, Kecamatan Tegallalang, Kabupaten Gianyar - Sade Devita Purnama Dewi; Ni Putu Anik Prabawati; I Dewa Ayu Putri Wirantari (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2023)
In the process of increasing village original income by utilizing the natural potential and plantations owned by Taro Village, the active role of the village government is required. One way that can be done is to form a village-owned enterprise (BUMDes). The purpose of this study was to determine the strategy of village-owned enterprises (BUMDes) in an effort to increase village original income (PADes). Based on the study using the theory of strategic management processes according to Wheelen and Hunger (2012) and SWOT analysis according to Rangkuti (2013), The results of this study show that the Sarwada Amwerta Village Owned Enterprise (BUMDes) has carried out a strategic management process, but there are several obstacles that prevent the Sarwada Amerta BUMDes from obtaining maximum income. The results of the SWOT matrix analysis produce three alternative strategies that can be used as alternative strategies for future strategic priorities, namely: (1) increasing BUMDes' human resources in the use of technology; (2) expanding collaboration with related parties; and (3) developing tourism units by collaborating. The results of this study show that researchers provide strategic recommendations for Sarwada Amerta Village-Owned Enterprises (BUMDes) in an effort to increase village original income